PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN, DAN KARAKTERISTIK SITUASI KERJA TERHADAP TINGKAT KEPUASAN KERJA KARYAWAN (STIE YPPI Rembang, 2012)
Abstract The research aims to test the effect of individual characteristic, job characteristic, and job of situation characteristic to level of job satisfaction official employee. This study uses the entire population of the official employee CV. Karya Pemuda Semarang obtained 104 people. The data analysis technique used is linear regression. Results of research refer that the individual characteristic, job characteristic, and job of situation characteristic have an influence positive to level of job satisfaction official employee.Keyword: Individual characteristic, Job characteristic, and Job of situation characteristic,